Pengaruh Asam Sitrat, Aluminium, dan Interaksinya Terhadap Pertumbuhan Kecambah Jagung Hibrida (Zea mays L.) Varietas Bisi- 18 - Wina Safutri; Zulkifli Zulkifli; Tundjung Tripeni Handayani (Jurnal Penelitian Pertanian Terapan, 2016)
The objective of this research was to know effect of citric acid, aluminum, and their itsinteraction on the seedling growth of hibrida maize (Zea mays L.) Var. Bisi-18. Theexperiment was conducted during January 2016 in Plant Physiology Laboratory,Department of Biology, Faculty of Mathematics and Natural Science, University ofLampung. The experiment was implemented in 2x3 factorial experiments. Factor A wasAluminum with 2 levels: 0 mM, 5 mM. Factor B was Citric Acid with 3 levels: 0 mM, 5 mM,and 10 mM. After selected corn seeds were soaked in citric acid solution for 24 hours, andgerminated in plastic tray. After 7 days seedlings were planted in plastic containers thatcontain aluminum solution. Variables in this research were shoot length, seedling freshweight, shoot root ratio, and relative water content after 7 days of growing period. Analysisof variance was conducted at 5% significant level. If interactions between aluminum andcitric acid was not significant, main effect was determined at 5% significant level with LSDtest. If interactions between aluminum and citric acid was significant, simple effect wasdetermined at 5% significant level with F test. The result showed that no aluminum effectobserved on all variables, and citric acid affected negativly all variables. No interctionsbetween aluminum and citric acid on all seedling growth variables of maize hibrida Var.Bisi-18. It is concluded aluminum 5mM was not able to cause stress in maize seedling. Inno stress condition citric acid has negative effect on maize seedling growth.Keyword: Citric acid, Aluminium, Maize Seedling, Shoot Length, Seedling Fresh Weight.